Clinical trials in pleural disease - Rahman, N; Najib M Rahman (2011)
The focus of this thesis is on practice changing clinical studies which impact upon the day to day treatment of patients with pleural infection, answering specific questions on several aspects of patient management. Specific areas of assessment in this thesis include: Assessment of the current evidence for optimal drain size choice in patients with pleural infection Analysis and statistical modelling of a previous cohort of patients with pleural infection, in order to assess optimal drain size choice in pleural infection The design, conduct and analysis of a 2 x 2 factorial multi-centre randomised, placebo controlled trial to assess the efficacy of two novel intrapleural agents (tPA and DNase) in aiding drainage in patients with pleural infection (The 2nd Multi-centre Intrapleural Sepsis Trial, referred to from here on as MIST2) Validation work informing the primary outcome measure of MIST2, assessing the relationship between chest radiograph imaging of infected pleural effusion and CT measured volume of pleural fluid using novel digital measurement strategies